2020
DOI: 10.3390/app10072570
|View full text |Cite
|
Sign up to set email alerts
|

Performance Comparison and Evaluation of Two Small Chili Pepper Harvester Prototypes That Attach to Walking Cultivators

Abstract: Two prototypes of small chili pepper harvesters that attach to walking cultivators were designed and manufactured before field performance tests were conducted. The two prototypes were designed and manufactured with different main frame materials, forms of divider, picking guides, and helix rotation speeds. The maximum helix speed of the first prototype was 500 rpm, and the helix rotation speeds of the second prototype were a minimum of 510 rpm and a maximum of 730 rpm. Field performance tests were conducted o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…Furthermore, most damaged hot peppers were recorded during transportation to the loading bay; thus, we suspect that too much force was applied to the hot pepper, resulting in the peppers being chopped and ripped out. Compared with a previous study on mechanical harvesting experiments, the damaged ratio observed in this study was much lower (8.37%) because the broader and blockier structure of the hot pepper ridges, characterized by the different planting distances, was more acceptable in managing the mechanical damage [10]. Furthermore, additional studies with fruit damage measurement in each harvester unit are required and would be done in the future.…”
Section: Damaged Hot Peppermentioning
confidence: 60%
See 1 more Smart Citation
“…Furthermore, most damaged hot peppers were recorded during transportation to the loading bay; thus, we suspect that too much force was applied to the hot pepper, resulting in the peppers being chopped and ripped out. Compared with a previous study on mechanical harvesting experiments, the damaged ratio observed in this study was much lower (8.37%) because the broader and blockier structure of the hot pepper ridges, characterized by the different planting distances, was more acceptable in managing the mechanical damage [10]. Furthermore, additional studies with fruit damage measurement in each harvester unit are required and would be done in the future.…”
Section: Damaged Hot Peppermentioning
confidence: 60%
“…As reported, the harvesting efficiency increased with an increase in the speed of the helix; however, pepper with twigs and damage rates also increased. Thus, successfully harvesting rates require improvements in all rotational speeds of the helix [10].…”
Section: Introductionmentioning
confidence: 99%
“…Kim et al [31] and Choi et al [40] measured the weights of harvested peppers, peppers without twigs, stem-attached peppers, damaged peppers, unharvested peppers, and damaged peppers. The performance of each pepper harvester was evaluated based on these measured weights.…”
Section: Analysis Methodsmentioning
confidence: 99%
“…When bigger particles, such as stemmed chili peppers, flow in from the picking part, the development of additional separating and sorting devices are required. Kim et al [31] obtained a PTR of 24.2-37.8% in a chili harvester comparison test, and suggested the need for a stem-separation and sorting device to reduce the input of additional manpower for sorting work after the chili harvest.…”
Section: Introductionmentioning
confidence: 99%
“…Kim et al of the National Institute of Agricultural Engineering and Chonbuk National University, Korea, designed and fabricated two prototypes of an unfolded double-helix-type pepper harvester attached to a walk-behind cultivator. These two prototypes were designed and built with different frame materials, dividers, picking rollers, and auger speeds to compare the two pepper harvester field harvests [5]. The rod comb tooth type [6]: Palau et al developed a hydraulically driven single-row pepper harvester mounted on a three-point suspension of a 35 to 45 kW tractor, which brushes the pepper from the plant by the counter-rotation of the brush drums and brushes the pepper fruits onto conveyor belts on both sides, which convey the pepper with a fan that scavenges for the magazines remaining in them.…”
Section: Introductionmentioning
confidence: 99%